Quality Analysis Of Low Quality Orthodox Black Tea At PT.Perkebunan Nusantara VIII Kebun Kertamanah Bandung, Jawa Barat - Sari, Dinda Nofita; Juwitaningtyas, Titisari (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
The purpose of this research are (1) Find out the control limits of the implementation of quality control on PT.Perkebunan Nusantara VIII Kebun Kertamanah. (2) to determine the production of low quality black tea products under controlled conditions in PT.Perkebunan Nusantara VIII Kebun Kertamanah. (3) to determine the factors that cause low quality black tea products to not meet the standards in PT.Perkebunan Nusantara VIII Kebun Kertamanah. (4) to find out the percentage value of off grade low quality black tea in PT.Perkebunan Nusantara VIII Kebun Kertamanah. The basic method is descriptive with the implementation method is the case study. Data were analyzed using (1) check sheet (2) p chart (3) fishbone diagram. The results showed that (1) control limits of low quality black tea which are in the upper and lower control limits. (2) production of low quality black tea products under controlled conditions (3) factors that cause low quality black tea products to not meet standards (4) value Percentage off grade low quality black tea in PT.Perkebunan Nusantara VIII Kebun Kertamanah.